High capacity Mg-re (la, ce) -ni-be-cu based solid state hydrogen storage composite and method of making
By adding rare earth elements La and Ce, as well as transition metals Ni and Be, to Mg-based alloys and using ZrF4 and La2O3 catalysts, a nanocrystalline Mg-RE(La,Ce)-Ni-Be-Cu-based solid hydrogen storage composite material was prepared. This solved the problems of thermodynamic stability and slow kinetics of Mg-based alloy hydrogen storage materials, and achieved a significant improvement in high capacity and low temperature hydrogen absorption and desorption performance.
Patent Information
- Application Number
- CN202511052297.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-29
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2045-07-29
AI Technical Summary
Existing Mg and Mg-based alloy hydrogen storage materials have high thermodynamic stability, complex activation processes, high dissociation temperatures, and slow hydrogenation/dehydrogenation kinetics, making it difficult to meet the practical application requirements of on-board hydrogen storage materials.
A hydrogen storage alloy of Mg90Ce3-xLaxNi7-y-zBeyCuz was used with the addition of ZrF4 and La2O3 catalysts. The nanocrystalline structure was formed by arc melting, rapid quenching of alloy strips and ball milling. Combined with the synergistic catalytic effect of rare earth elements La and Ce, the hydrogen absorption and desorption performance was improved.
It significantly improves the hydrogen absorption and desorption performance of hydrogen storage materials, reduces the deionization temperature, simplifies the activation process, and achieves high-capacity hydrogen storage performance, making it suitable for large-scale preparation and application.
Smart Images

Figure CN120903436B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid hydrogen storage materials technology, and in particular to a high-capacity Mg-RE(La,Ce)-Ni-Be-Cu based solid hydrogen storage composite material and its preparation method. Background Technology
[0002] Clean energy, widely used in automobiles, is generally considered an attractive strategy for controlling environmental pollution and reducing over-reliance on fossil fuels. Among existing clean energy sources, hydrogen energy, with its inexhaustible supply, zero greenhouse gas emissions, and high energy efficiency, is considered a promising renewable energy source. In a sense, whether hydrogen fuel cell vehicles can achieve widespread commercial application in the 21st century depends almost entirely on the availability of a safe, economical, and practical hydrogen storage technology. Currently, among all hydrogen storage methods, metal hydride storage is considered the preferred solution to meet the requirements of mobile applications, with Mg and Mg-based alloys being the preferred materials for on-board hydrogen fuel cells.
[0003] However, some inherent defects of Mg and Mg-based alloys, such as relatively high hydrogen desorption temperatures and slow hydrogenation / dehydrogenation kinetics, severely limit their practical application as on-board hydrogen storage materials, and they cannot meet all the performance requirements put forward by the U.S. Department of Energy (DOE) for vehicle applications.
[0004] Therefore, further improving the hydrogen storage performance of Mg-based alloys remains a significant challenge for researchers in this field. Summary of the Invention
[0005] Based on the above analysis, the present invention aims to provide a high-capacity Mg-RE(La,Ce)-Ni-Be-Cu based solid hydrogen storage composite material and its preparation method, in order to solve at least one of the problems of high thermodynamic stability, complex activation process, high dissociation temperature, and slow hydrogenation / dehydrogenation kinetics in existing magnesium-based hydrogen storage materials.
[0006] On one hand, embodiments of the present invention provide a high-capacity Mg-RE(La,Ce)-Ni-Be-Cu-based solid-state hydrogen storage composite material, wherein the hydrogen storage composite material contains Mg 90 Ce 3-x La x Ni 7-y-z Be y Cu z A hydrogen storage alloy and a catalyst comprising 2-8 wt% of the alloy, the catalyst comprising ZrF4 and La2O3, wherein 0.5 ≤ x ≤ 3, 0 <y≤2,0.5≤z≤5。
[0007] Furthermore, the hydrogen storage composite material contains Mg 90 Ce3-x La x Ni 7-y-z Be y Cu z The hydrogen storage alloy and a catalyst comprising 4-6 wt% of the alloy weight, the catalyst comprising ZrF4 and La2O3, wherein 0.5 ≤ x ≤ 2.5, 0.5 ≤ y ≤ 2, and 2 ≤ z ≤ 4.
[0008] Furthermore, x:y:z = 1.5-2:0.5-1.5:2-3, and the catalyst accounts for 4-6 wt% of the alloy weight.
[0009] Furthermore, the mass ratio of ZrF4 to La2O3 is 1:0.95 to 1:1.05.
[0010] Furthermore, the hydrogen storage alloy has a nanocrystalline structure with an average grain size of 20-100 nm.
[0011] Furthermore, the hydrogen storage alloy contains intermetallic compounds Mg2Ni phase, LaNi3 phase, MgCe phase and CuBe phase.
[0012] On the other hand, embodiments of the present invention provide a method for preparing the hydrogen storage composite material, comprising:
[0013] S1: Mg is composed according to the preset chemical formula. 90 Ce 3-x La x Ni 7-y-z Be y Cu z When preparing the ingredients, a certain proportion of loss on ignition should be added when weighing Mg, La, and Ce.
[0014] S2. Place the prepared raw materials in the magnesium oxide crucible in sequence, melt the raw materials by electric arc melting, induction heating melting or other heating methods, and pour the molten alloy into the copper mold to obtain the master alloy ingot.
[0015] S3. Place the ingot prepared in S2 inside a quartz tube with a slit at the bottom, and induction heat it until the ingot is completely melted. Use the pressure of the protective gas to spray the liquid alloy from the slit at the bottom of the quartz tube onto the surface of a rotating water-cooled copper roller to form a fast-quenched alloy strip.
[0016] S4. After mechanically crushing the fast-quenched alloy strip and passing it through a 200-mesh sieve, the alloy particles remaining on the sieve are loaded into a ball mill jar together with the catalyst ZrF4+La2O3 and stainless steel grinding balls. After ball milling, Mg-RE(La,Ce)-Ni-Be-Cu based solid hydrogen storage composite material is obtained.
[0017] Furthermore, in step S1, Mg, La and Ce are additionally added as a loss-on-burn amount of 5%-10% of their calculated mass during batching.
[0018] Further, in step S2, the specific steps of the melting operation are as follows: the weighed bulk metal is placed in the magnesium oxide crucible of the medium-frequency induction furnace according to the designed process; bulk rare earth elements La, Ce, and electrolytic Cu are placed at the bottom of the crucible; bulk Be and Ni plates are placed on top of the electrolytic Cu; and bulk Mg is placed on the top layer; a vacuum is drawn to 1×10⁻⁶. -2 -5×10 -5 A pressure of 0.01-0.1 MPa is introduced as a protective gas, which is high-purity helium or a helium-argon mixture with a volume ratio of 1:1. The temperature is then increased to 1500-1600℃ to obtain molten Mg. 90 Ce 3-x La x Ni 7-y-z Be y Cu z Liquid master alloy, hold for 1-5 minutes.
[0019] Furthermore, in step S3, the linear speed of the water-cooled copper roller is 10-20 m / s, and the thickness of the formed fast-quenched alloy strip is 100-350 μm, and the width is 2-30 mm.
[0020] Furthermore, in step S4, the specific steps of ball milling are as follows: after evacuating the ball mill jar, fill it with high-purity argon gas, and ball mill in an all-around planetary high-energy ball mill for 2-7 hours, with a ball-to-material ratio of 45:1 to 35:1 and a rotation speed of 330 to 350 rpm; during the ball milling process, the ball mill is stopped for 0.5 hours every 1 hour of operation.
[0021] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0022] 1. The hydrogen storage composite material disclosed in this invention possesses high hydrogen storage capacity and excellent hydrogen absorption and desorption performance. This invention improves the hydrogen storage performance of the alloy by alloying it with trace amounts of rare earth elements La and Ce, metals Ni, Be, and Cu, forming multiple second phases within the alloy. On one hand, the addition of rare earth elements and various metals causes the formation of multiple intermetallic compounds in the Mg-based alloy: Mg and Ni form the Mg2Ni phase, La and Ni form the LaNi3 phase, Mg and Ce form the MgCe phase, and Cu and Be form the CuBe phase. These intermetallic compounds significantly improve the thermodynamics and kinetics of hydrogen absorption and desorption in the Mg-based alloy by increasing the phase boundary density. On the other hand, rare earth elements La, Ce, and metal Be can form LaH3, CeH3, and BeH2 hydrides with hydrogen, which can serve as nucleation sites for the formation and decomposition of magnesium-based hydrides, improving the hydrogen absorption and desorption kinetics of the Mg-based alloy and exhibiting significant catalytic effects.
[0023] 2. The surface state of hydrogen storage materials has a significant impact on solid-state hydrogen storage. In this invention, after mechanically crushing the rapidly quenched alloy sheet, a small amount of (ZrF3+La2O3) catalyst is added and ball milling is performed for a short time. While maintaining the microstructure of the rapidly quenched alloy, the surface state of the rapidly quenched alloy is improved, resulting in a significant increase in surface roughness and the appearance of high-density crystal defects. This further improves the thermodynamics and kinetics of hydrogen absorption and desorption of the alloy / composite material.
[0024] 3. The composite hydrogen storage material disclosed in this invention has good hydrogen absorption and desorption kinetics and thermodynamic properties. Compared with existing hydrogen storage materials, its thermodynamic stability is significantly reduced (i.e., excellent hydrogen desorption kinetics) and its dissociation temperature is reduced (i.e., it has better hydrogen absorption and desorption performance, especially hydrogen desorption performance, at the same temperature). Moreover, the composite hydrogen storage material can be obtained without a complicated activation process.
[0025] 4. The preparation process and equipment / instruments of the composite hydrogen storage material of the present invention all adopt current mature operations and equipment, which are easy to implement. Various raw materials are readily available and suitable for large-scale preparation and wide-ranging applications.
[0026] In this invention, the above-described technical solutions can be combined with each other to achieve more preferred combinations. Other features and advantages of this invention will be set forth in the following description, and some advantages may become apparent from the description or be learned by practicing the invention. The objects and other advantages of this invention can be realized and obtained from what is particularly pointed out in the description and drawings. Attached Figure Description
[0027] The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. Throughout the drawings, the same reference numerals denote the same parts.
[0028] Figure 1 This is the rapidly quenched alloy strip from Example 1;
[0029] Figure 2 The XRD diffraction patterns of the as-cast alloys in Examples 1-6 are shown below.
[0030] Figure 3 The SEM morphology of the ball-milled composite powders in Examples 1-6 is shown.
[0031] Figure 4 The XRD diffraction patterns of the ball-milled composite powders in Examples 1-6 are shown below.
[0032] Figure 5 The HRTEM morphology of the ball-milled composite powders in Examples 1-6 is shown. Detailed Implementation
[0033] The preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings, which constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not intended to limit the scope of the present invention.
[0034] Mg and Mg-based alloy solid hydrogen storage materials, which are the preferred materials for on-board hydrogen fuel cells, have some inherent drawbacks, such as relatively high hydrogen desorption temperatures and slow hydrogenation / dehydrogenation kinetics, which severely limit their practical application as on-board hydrogen storage materials. Currently, the main methods for addressing these issues focus on two aspects: reducing the size of Mg and Mg-based particles, and adding rare earth elements, transition metal elements, or catalysts to Mg or Mg-based alloys. However, to date, there are few studies and reports on improving Mg-based alloy solid hydrogen storage materials, and the rare earth elements used to dope Mg-based alloys are relatively scarce and expensive metals, resulting in high costs and making them unsuitable for large-scale industrial production and application. This significantly limits the application of Mg-based alloys as on-board solid hydrogen storage materials for clean energy vehicles.
[0035] Therefore, the present invention provides a high-capacity Mg-RE(La,Ce)-Ni-Be-Cu based solid hydrogen storage composite material, wherein the hydrogen storage composite material contains Mg 90 Ce 3-x La x Ni 7-y-z Be y Cu z A hydrogen storage alloy and a catalyst comprising 2-8 wt% of the alloy, the catalyst comprising ZrF4 and La2O3, wherein 0.5 ≤ x ≤ 3, 0 <y≤2,0.5≤z≤5。
[0036] This invention reveals that the substitution of Mg with rare earth elements La and Ce, as well as metallic elements Ni, Cu, and Be, can reduce the thermal stability of Mg-based alloy hydrides and improve their hydrogen absorption and desorption kinetics. The specific mechanisms of action for each component are as follows:
[0037] La and Ce: Adding trace amounts of rare earth elements La and Ce to Mg-based alloys can significantly reduce the thermal stability of hydrides and improve the hydrogen absorption and desorption kinetics of the alloy. On the one hand, the added La and Ce can form LaH3 and CeH2 during the hydrogen absorption process of Mg-based alloys. 2.73 These two rare earth hydrides possess high thermal stability. Although they do not directly participate in the hydrogen absorption and desorption process, their dispersed distribution in the alloy allows them to act as nucleation sites for the hydrogen absorption and desorption reactions, thus accelerating the reaction rate and acting as catalysts. Furthermore, the combined addition of these two elements has a synergistic catalytic effect (1+1>2), further enhancing the catalytic activity. On the other hand, the added rare earth elements La and Ce have a stronger attraction to H than Mg, significantly reducing the Mg-H bond strength and lowering the thermodynamic stability of the magnesium-based hydrides, thereby reducing the hydrogen desorption temperature to some extent. Additionally, the addition of La and Ce to the Mg-based alloy can form LaNi3 and MgCe phases in situ with Ni and Mg, respectively. These LaNi3 and MgCe phases precipitate at the boundary between Mg2Ni and CuBe, which is beneficial for the formation of the main phase. It should be noted that the rare earth elements La and Ce have a high specific gravity; excessive addition of La and Ce will inevitably significantly reduce the mass hydrogen storage density of the alloy. Therefore, this invention controls the total amount of rare earth elements added to the alloy to 3% atomic percentage.
[0038] Ni: The addition of Ni can lower the hydrogen desorption temperature and increase the hydrogen desorption rate of the alloy. Specifically, Ni reduces the dissociation energy of H2 molecules on the magnesium surface to form hydrogen atoms, and improves the hydrogen absorption and desorption kinetics of the alloy. Its catalytic effect in magnesium-based alloys mainly includes two aspects: First, Ni added to the Mg-based alloy reacts with Mg in situ to form the Mg2Ni phase. The Mg2Ni phase itself is an excellent solid-state hydrogen storage material with particularly good reversible hydrogen storage performance and can directly participate in the hydrogen absorption and desorption reactions of the Mg-based alloy. Simultaneously, the Mg2Ni phase can serve as a nucleation site for the hydrogen absorption and desorption reactions of the magnesium-based alloy, thereby improving the hydrogen absorption and desorption kinetics of the alloy. It should be noted that Ni itself is not a hydride-forming element and has a relatively high specific gravity. Excessive addition will inevitably lead to a significant decrease in the mass hydrogen storage density of the Mg-based hydrogen storage material. Furthermore, Ni is a noble metal element, and the use of large amounts of Ni will inevitably lead to a significant increase in the cost of Mg-based hydrogen storage materials. Therefore, this invention controls the amount of Ni added to the alloy to less than 6.5% atomic percentage.
[0039] Cu plays a similar role to Ni in Mg-based alloys. Both are transition metal elements that provide active sites for the bonding of Mg and H. However, the catalytic effect of Cu is far less than that of Ni. The combined addition of Ni and Cu, compared to the addition of a single transition metal element, can significantly improve the hydrogen storage performance of Mg-based alloys through synergy. It should be noted that the addition of excessive Cu may form MgCu2 or Mg2Cu phases. Neither of these phases can form hydrides and consumes magnesium in the alloy, inevitably leading to a significant decrease in the hydrogen storage capacity of the alloy. Therefore, this invention controls the amount of Cu added to the alloy within the range of 0.5-5% atomic percentage.
[0040] Be: The addition of Be to the alloy can improve the hydrogen storage performance of magnesium-based alloys, mainly in two aspects: First, Be itself is a hydrogen-absorbing element and can form the BeH2 phase. The appearance of this phase can provide nucleation sites for the formation and decomposition of Mg-based hydrides, improving the hydrogen absorption and desorption kinetics of the alloy. Second, the combined addition of Be and Cu can form the CuBe phase, increasing the phase boundary density of the alloy and improving the hydrogen absorption and desorption kinetics. It should be noted that although Be is a lightweight element and the addition of Be will not significantly reduce the mass hydrogen storage density of Mg-based alloys, excessive Be will produce a separate enriched phase, leading to agglomeration and hindering hydrogen from entering the magnesium alloy, further affecting the hydrogen storage performance. Therefore, this invention controls the amount of Be added to the alloy within the range of 2% atomic percentage.
[0041] ZrF4: As a catalyst, ZrF4 has very low hardness and good stability. It has a good lubricating effect during ball milling, which can effectively prevent the agglomeration of matrix alloy particles and their adhesion to the inner wall of the ball mill jar, thereby improving the ball milling efficiency. In addition, the ZrF4 nanoparticles after ball milling are mainly distributed on the surface of Mg-based alloy particles, which can improve the surface activity of the matrix alloy, thereby improving the activation performance and hydrogen absorption and desorption kinetics of the composite material.
[0042] La2O3: As a catalyst, La2O3 has high hardness and good structural stability. During ball milling, it has a significant cutting effect on the matrix alloy particles, making the ball-milled alloy particles smaller and significantly improving the efficiency of ball milling. Under the external force of the grinding balls, the high-hardness La2O3 nanoparticles are easily embedded in the soft matrix alloy. This special structure causes the phase interface of Mg-based alloy particles to grow explosively, providing a good channel for the dissociation of hydrogen molecules and the diffusion of hydrogen atoms.
[0043] As can be seen, the two highly stable catalysts, ZrF4 and La2O3, added to the Mg-based alloy in this invention are uniformly distributed on the surface and inside of the material particles, respectively. This enables the formation of numerous active interfaces between the alloy and the catalyst. These interfaces not only provide excellent nucleation sites for the formation and decomposition of hydrides but also offer good channels for the dissociation of hydrogen molecules and the diffusion of hydrogen atoms. Therefore, the combined addition of ZrF4 and La2O3, two catalysts with different properties, can significantly improve the hydrogen absorption and desorption kinetics of the magnesium-based alloy. Preliminary experimental data show that when the mass ratio of the two catalysts reaches 1:0.95 to 1:1.05, the catalytic performance is excellent. It should be noted that the catalyst itself does not absorb hydrogen; the addition of excessive catalyst will inevitably lead to a significant decrease in the hydrogen storage capacity of the base alloy. In terms of weight percentage, this invention controls the amount of catalyst within the range of 2-8 wt% of the weight of the Mg-based alloy, which can be 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, or 8 wt%.
[0044] It should be noted that, in order to improve the hydrogen absorption and desorption kinetics and cycle stability of Mg-based alloys, this invention requires control of the grain structure of Mg-based alloys, including morphology and size.
[0045] Specifically, the Mg-based alloy has a nanocrystalline structure with an average grain size of 20-100 nm. Compared with microcrystalline and amorphous structures, the nanocrystalline structure shortens the hydrogen diffusion path due to its smaller size, increases the number of active sites on the surface and interface due to its higher specific surface area, provides more diffusion channels for hydrogen atoms due to its higher grain boundary density, and lowers the activation energy of the MgH2 hydrogen adsorption and desorption reaction due to its high specific surface area and interfacial energy. This promotes the adsorption and dissociation of hydrogen molecules, increases the hydrogen adsorption and desorption rate, reduces the kinetic barriers to the hydrogen adsorption and desorption reaction, and reduces thermodynamic stability. Furthermore, the high grain boundary density results in a higher number of crystal defects in the Mg-based alloy. The micro / nanocrystalline structure and crystal defects in the alloy obtained through melting exhibit high stability, and the grains do not easily grow after multiple hydrogen adsorption and desorption cycles. Therefore, the Mg-based alloy not only possesses excellent hydrogen adsorption and desorption kinetics but also good cycle stability.
[0046] More specifically, the volume percentage of nanocrystalline structures in the Mg-based alloy described in this invention is 85-93%. Due to limitations in current manufacturing processes, the Mg-based alloy also contains a small amount of amorphous structures, such as... Figure 1 , 4 As shown in Figure 5.
[0047] According to some preferred embodiments of the present invention, the average grain size of the Mg-based alloy nanocrystals can be any value in the range of 20-100nm, such as 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, and 100nm.
[0048] This invention also provides a method for preparing the above-mentioned Mg-RE(La,Ce)-Ni-Be-Cu based solid hydrogen storage composite material, the specific steps of which are as follows:
[0049] S1: Mg is composed according to the preset chemical formula. 90 Ce 3-x La x Ni 7-y-z Be y Cu z When preparing the ingredients, a certain proportion of loss due to burn is added when weighing Mg, La, and Ce, and the metal purity of the raw materials is ≥99.5%.
[0050] S2. Place the prepared raw materials in the magnesium oxide crucible in sequence, melt the raw materials by electric arc melting, induction heating melting or other heating methods, and pour the molten alloy into the copper mold to obtain the master alloy ingot.
[0051] S3. Place the ingot prepared in S2 inside a quartz tube with a slit at the bottom, and induction heat it until the ingot is completely melted. Use the pressure of the protective gas to spray the liquid alloy from the slit at the bottom of the quartz tube onto the surface of a rotating water-cooled copper roller to form a fast-quenched alloy strip.
[0052] S4. After mechanically crushing the fast-quenched alloy strip and passing it through a 200-mesh sieve, the alloy particles remaining on the sieve are loaded into a ball mill jar together with the catalyst ZrF4+La2O3 and stainless steel grinding balls. After ball milling, Mg-RE(La,Ce)-Ni-Be-Cu based solid hydrogen storage composite material is obtained.
[0053] Specifically, since the metals Mg and rare earth elements La and Ce have low melting points and are easily volatilized, in step S1, a certain amount of loss on ignition needs to be added for the elements Mg, La and Ce during the batching process, which is 5%-10% by mass.
[0054] According to some preferred embodiments of the present invention, the loss on ignition of the additional elements Mg, La and Ce added during the preparation can be 5%, 6%, 7%, 8%, 9% or 10% by mass.
[0055] Specifically, in step S2, the weighed bulk metal is placed in the MgO crucible of the medium-frequency induction furnace according to the designed process. Bulk rare earth elements La, Ce, and electrolytic Cu are placed at the bottom of the crucible, bulk Be and Ni plates are placed on top of electrolytic Cu, and bulk Mg is placed on top. This arrangement order is determined by the melting point and electromagnetic induction efficiency of the raw material metals. This arrangement of raw materials can effectively improve the metal smelting efficiency, make the alloy composition more stable, the element distribution more uniform, and improve the yield of finished products.
[0056] Specifically, in step S2, the heating conditions are as follows: the crucible is evacuated to a vacuum of 1×10⁻⁶. -2 -5×10 -5 A pressure of 0.01-0.1 MPa is introduced as a protective gas, which is high-purity helium or a helium-argon mixture with a volume ratio of approximately 1:1. The temperature is then increased to 1500-1600℃ to obtain molten Mg. 90 Ce 3-x La x Ni 7-y-z Be y Cu z The liquid master alloy is held at a temperature of 1-5 minutes to homogenize its composition.
[0057] Specifically, in step S3, the linear speed of the water-cooled copper roller is 10-20 m / s, for example, 10 m / s, 12 m / s, 15 m / s, 18 m / s, or 20 m / s. By adjusting the rotational speed (quenching speed) of the copper roller, the crystal structure of the alloy can be controlled. Too low a quenching speed will inevitably increase the thickness of the rapid quenching band, resulting in a large number of microcrystals; too high a quenching speed will result in a thin rapid quenching band, easily leading to the formation of an amorphous state. The presence of a large number of microcrystals and amorphous phases will significantly affect the hydrogen absorption and desorption properties of the alloy. The thickness of the rapid quenching band is determined by the rotational speed of the copper roller; the higher the speed, the smaller the thickness of the rapid quenching band. The width of the rapid quenching band does not directly affect the properties of the alloy.
[0058] According to some preferred embodiments of the present invention, by controlling the linear speed of the water-cooled copper roller rotation in the range of 10-20 m / s, the thickness of the rapidly quenched alloy strip formed is 100-350 μm and the width is 2-30 mm (the width depends on the length of the nozzle at the bottom of the quartz tube).
[0059] Specifically, in step S3, the setting of the slit width at the bottom of the quartz tube is a key technical parameter. It is necessary to ensure that the liquid metal will not flow out of the slit without external force (i.e., its own weight) and can be smoothly ejected from the slit under appropriate external force (i.e., protective gas pressure). If the pressure is too low, the alloy will not flow out, and if the pressure is too high, the quartz tube will burst. Generally speaking, the slit width at the bottom of the quartz tube is 0.3±0.005mm, and the pressure of the protective gas is 1.05±0.003atm.
[0060] According to some preferred embodiments of the present invention, the present invention employs melt rapid quenching to obtain a structure with ultrafine grains (average grain size <100nm), specifically 20-100nm, which can be 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, or 100nm. Moreover, the rapidly quenched structure contains a high density of crystal defects, including dislocations, stacking faults, twins, and numerous grain boundaries. This microstructure is extremely beneficial for improving the thermodynamic and kinetic properties of the alloy. Furthermore, unlike ball milling, the ultrafine structure and crystal defects obtained by rapid quenching have high stability. After multiple hydrogen absorption and desorption cycles, the grains are not prone to aggregate and grow, which is reflected in the excellent cycle stability of the alloy in terms of hydrogen absorption and desorption performance.
[0061] Specifically, in step S4, the specific steps of ball milling are as follows: the rapidly quenched alloy strip obtained in step S3 is mechanically crushed and then passed through a 200-mesh sieve; the sieved alloy powder, catalyst, and grinding balls are loaded into a ball mill jar; the ball mill jar is evacuated and then filled with high-purity argon gas, and ball milled in an all-around planetary high-energy ball mill for 2-7 hours, with a ball-to-material ratio of 20:1 and a rotation speed of 350 r / min; during the ball milling process, the ball mill is stopped for 0.5 hours every 1 hour of operation.
[0062] It should be noted that using a suitable ball-to-material ratio and an appropriate rotation speed is to obtain the best ball milling efficiency; an appropriate ball milling time is to obtain particles with as many nanocrystalline particles as possible (e.g., ...). Figure 5 (As shown); The hydrogen absorption and desorption properties of the alloy are controlled by the diffusion rate of hydrogen atoms in the material matrix. Grain boundaries can provide good channels for hydrogen atom diffusion. The nanocrystalline structure has the highest grain boundary density, which has unique benefits for hydrogen atom diffusion.
[0063] Specifically, in step S4, the ball milling time is 2-7 hours, which can be 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, or 7 hours. If the ball milling time is too short, the grain size will be too large, failing to meet the required grain size and the ideal bonding between the catalyst and the matrix material, thus affecting the catalytic effect. If the ball milling time is too long, a large number of amorphous structures will appear. Moreover, the longer the ball milling time, the lower the material preparation efficiency and the more likely the ball milled material will aggregate or even weld together, significantly reducing the hydrogen storage performance. The stoppage during the ball milling process is to prevent the grinding balls and abrasive from overheating.
[0064] It should be noted that after adding the two catalysts (ZrF4 + La2O3) and ball milling for a short time, the surface state of the alloy was improved while basically maintaining the microstructure of the rapidly quenched alloy, thus leveraging the advantages of both preparation processes. During ball milling, the two catalysts are uniformly distributed on the surface of the alloy particles and in the matrix, fully utilizing their combined catalytic effect to improve the thermodynamic and kinetic properties of hydrogen absorption and desorption in the alloy. The catalytic effect of ZrF4 mainly lies in its very low hardness and good stability, providing excellent lubrication during ball milling and effectively preventing abrasive aggregation and adhesion to the inner wall of the ball mill jar. After ball milling, ZrF4 is mainly distributed on the surface of the matrix alloy particles, improving the surface activity of the matrix alloy. The catalytic effect of La2O3 lies in its high hardness, which has a significant cutting effect on the alloy particles during ball milling, resulting in finer particles. After ball milling, La2O3 is mainly embedded within the matrix alloy particles, generating a large number of highly active phase interfaces. After ball milling, the addition of two highly stable catalysts allows for uniform distribution on the surface and within the material particles, inevitably forming numerous active interfaces between the alloy and the catalyst. These interfaces provide excellent nucleation sites for hydride formation and decomposition. This invention combines rapid quenching, ball milling, and catalyst addition, significantly improving the thermodynamics and kinetics of hydrogen absorption and desorption in the alloy (as shown in Table 2). It is important to note that the catalyst itself does not absorb hydrogen; excessive catalyst addition will inevitably lead to a significant decrease in the hydrogen storage capacity of the base alloy. By weight percentage, this invention controls the amount of catalyst within the range of 2-8 wt% of the Mg-based alloy.
[0065] The following specific embodiments illustrate the high-capacity Mg-RE(La,Ce)-Ni-Be-Cu-based hydrogen storage alloy catalyzed by the ZrF4+La2O3 composite catalyst of the present invention and its preparation method.
[0066] Examples 1-6 and Comparative Examples 1-3 all employed the following method to prepare high-capacity Mg-RE(La,Ce)-Ni-Be-Cu based hydrogen storage composite materials:
[0067] S1. After selecting bulk metal and grinding to remove the surface oxide layer, weigh out bulk metal Mg, rare earth metals La and Ce, electrolytic Ni, metal Cu and Be according to the chemical formula composition of Mg-based hydrogen storage alloys in each embodiment or comparative example, with metal purity ≥99.5%; wherein, during the batching, increase the proportion of metal Mg by 8% and rare earth La and Ce by 5% each to compensate for the burn-off during smelting;
[0068] S2. Place the prepared raw materials in the magnesium oxide crucible in the following order: place the blocky rare earth La, Ce and electrolytic Cu at the bottom of the crucible, place the blocky Be and Ni plates on top of the electrolytic Cu, and place the blocky Mg on the top.
[0069] After evacuation, a protective gas is introduced and induction heating is performed. Specifically, the crucible is evacuated to a vacuum level of 1×10⁻⁶. -2 -5×10 -5 A pressure of 0.01-0.1 MPa is introduced as a protective gas, which is high-purity helium or a helium-argon mixture with a volume ratio of approximately 1:1. The temperature is then increased to 1500-1600℃ to obtain molten Mg. 90 Ce 3-x La x Ni 7-y-z Be y Cu z The liquid master alloy is held at a temperature of 1-5 minutes to homogenize its composition, thus obtaining a molten liquid master alloy.
[0070] The liquid master alloy is poured into a copper mold to obtain a master alloy ingot;
[0071] S3. The ingot prepared in S2 is placed inside a quartz tube with a slit at the bottom and induction heated until the ingot is completely melted. The pressure of the protective gas is used to spray the liquid alloy from the slit at the bottom of the quartz tube onto the surface of a rotating water-cooled copper roller to form a fast-quenched alloy strip. The slit width is 0.3±0.005mm, the surface linear velocity of the fast-quenched water-cooled copper roller is 10-20m / s, and the pressure of the protective gas is 1.05±0.003atm, resulting in a fast-quenched alloy strip with a thickness between 100-350μm.
[0072] S4. The rapidly quenched thin strip obtained in S3 is mechanically crushed and passed through a 200-mesh sieve. It is then mixed with 2-8 wt% of the alloy weight of catalyst ZrF4+La2O3 and stainless steel grinding balls with a ball-to-material ratio of 20:1 and loaded into a stainless steel ball mill jar. The mixture is then ball-milled in an all-around planetary ball mill for 2-7 hours at a speed of 350 r / min. The ball mill is stopped for 0.5 hours after every 1 hour of continuous operation to obtain ball-milled powder, which is the hydrogen storage composite material.
[0073] The chemical composition and process parameters of each specific embodiment and comparative example are shown in Table 1.
[0074] Table 1 Chemical composition and process parameters of Examples 1-6 and Comparative Examples 1-3
[0075]
[0076] Structural analysis and performance testing: The phase structure of the cast and ball-milled powders was tested by XRD. The morphology and microstructure of the cast and ball-milled alloys were observed by high-resolution transmission electron microscopy (HRTEM) and scanning electron microscopy (SEM), and the crystal state of the alloy was determined by selected area electron diffraction (SAED). The hydrogen absorption activation performance, hydrogen storage capacity, and hydrogen absorption and desorption kinetics of the alloy powder were tested using a semi-automatic Sieverts system: the hydrogen absorption temperature was 270℃, the initial hydrogen pressure was 3 MPa, the hydrogen desorption temperature was 270℃, and the hydrogen desorption rate was 1×10⁻⁶ MPa. -4 The test was conducted at a pressure of MPa.
[0077] Figure 1 The rapid quenching alloy strip of Example 1 has an average thickness of about 105 μm. TEM observation revealed that the structure of the rapid quenching alloy strip is nanocrystalline with a small amount of amorphous structure.
[0078] Figure 2 The XRD patterns of the as-cast alloys in Examples 1-6 show that the addition of Ni, Cu and Be to alloy the alloys resulted in the formation of various intermetallic compounds: Mg2Ni phase, LaNi3 phase, MgCe phase and CuBe phase.
[0079] Figure 3 The SEM images of the ball-milled powders from Examples 1-6 show that the alloy particles exhibited excellent dispersion after ball milling, with no obvious agglomeration. No free catalyst ZrF4+La2O3 was found, suggesting that it was uniformly distributed on the surface and inside the ball-milled alloy particles. Since ZrF4 is very soft, it would not penetrate the interior of the alloy particles during ball milling. However, La2O3 is very hard, and its particles are highly likely to penetrate the interior of the ball-milled alloy particles during the process.
[0080] Figure 4 The XRD patterns of the ball-milled powders from Examples 1-6 show that the ball-milled materials have nanocrystalline and amorphous structural features.
[0081] Figure 5 The HRTEM morphology of the ball-milled alloys in Examples 1-6 shows that the alloys have nanocrystalline and amorphous structures.
[0082] The hydrogen absorption and release capacity and kinetics of the alloy powders in the examples and comparative examples were tested using a fully automated Sieverts system. The results are shown in Table 2.
[0083] Table 2 Hydrogen absorption / desorption kinetics and cycling stability of alloy powders with different compositions
[0084]
[0085]
[0086] Cmax —Saturated hydrogen absorption (wt.%) at an initial hydrogen pressure of 3 MPa and a temperature of 270 °C; —Hydrogen absorption (wt.%) within 5 minutes at an initial hydrogen pressure of 3 MPa and a temperature of 270 °C. —At an initial pressure of 1×10 -4 Hydrogen release (wt.%) within 20 minutes at MPa and 270℃.
[0087] The above results indicate that the Mg-based alloy powders prepared in Examples 1-6 of this invention possess high hydrogen absorption and desorption capacities and excellent kinetic properties. In particular, the alloys exhibit good hydrogen desorption performance at relatively low temperatures. Furthermore, the Mg-based alloy powders simultaneously satisfy the following conditions: under an initial hydrogen pressure of 3 MPa and a temperature of 270°C, the saturated hydrogen absorption capacity C... max >5.70 wt.%, hydrogen absorption within 5 minutes With an initial pressure of 1×10 -4 At a pressure of MPa and a temperature of 270°C, the hydrogen release rate within 20 minutes is greater than 5.40 wt.%.
[0088] Compared with Example 1, Comparative Example 1 had the same alloy composition, but no catalyst was added during the ball milling process. Its hydrogen storage capacity and hydrogen absorption and desorption kinetics were lower than those of Example 1, which shows the role of the catalyst in improving the hydrogen absorption and desorption performance of the material.
[0089] Compared with Example 1, Examples 7 and 8 both meet the requirements of the present invention in terms of alloy composition and catalyst addition. However, if the ball milling time is too short or too long, the hydrogen absorption and desorption kinetics performance will decrease to varying degrees, showing the influence of ball milling time on the hydrogen storage performance of the material.
[0090] In summary, this invention reduces the stability of Mg-based hydrides and improves their hydrogen absorption and desorption kinetics by adding multi-element rare earth elements La and Ce, as well as transition metal elements Ni, Be, and Cu. The rapid quenching of alloy sheets using mechanical methods, the addition of a small amount of catalyst (ZrF4 + La2O3), and subsequent mechanical ball milling for an appropriate time further improve the thermodynamics and kinetics of hydrogen absorption and desorption. The hydrogen storage material powder prepared by this invention possesses excellent hydrogen absorption and desorption capacity and good thermodynamic and kinetic properties, demonstrating high application potential in the field of hydrogen fuel cell hydrogen supply carriers. Furthermore, the alloy preparation process is simple and easy to operate, fully meeting the requirements for large-scale production.
[0091] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.
Claims
1. A high-capacity Mg-RE(La,Ce)-Ni-Be-Cu based solid-state hydrogen storage composite material, characterized in that, The hydrogen storage composite material contains Mg 90 Ce 3-x La x Ni 7-y-z Be y Cu z The hydrogen storage alloy and a catalyst comprising 2-8 wt% of the alloy weight, wherein the catalyst comprises ZrF4 and La2O3, wherein 0.5 ≤ x ≤ 2.5, 0.5 ≤ y ≤ 2, and 2 ≤ z ≤ 4; The hydrogen storage alloy contains intermetallic compounds Mg2Ni phase, LaNi3 phase, MgCe phase and CuBe phase; The hydrogen storage alloy has a nanocrystalline structure with an average grain size of 20-100 nm, and the volume ratio of the nanocrystalline structure is 85-93%. The mass ratio of ZrF4 to La2O3 is 1:0.95 to 1:1.05; The method for preparing the hydrogen storage composite material includes: Mg 90 Ce 3-x La x Ni 7-y-z Be y Cu z The hydrogen storage alloy ingot is placed inside a quartz tube with a slit at the bottom and induction heated until the ingot is completely melted. The pressure of the protective gas is used to spray the liquid alloy from the slit at the bottom of the quartz tube onto the surface of a rotating water-cooled copper roller to form a rapid quenching alloy strip. The linear speed of the water-cooled copper roller is 10-20 m / s, and the thickness of the rapid quenching alloy strip is 100-350 μm. After mechanically crushing the rapid-quenched alloy strip and passing it through a 200-mesh sieve, the alloy particles remaining on the sieve are loaded into a ball mill jar together with the catalyst ZrF4+La2O3 and stainless steel grinding balls. After ball milling, Mg-RE(La,Ce)-Ni-Be-Cu based solid hydrogen storage composite material is obtained. The ball milling is carried out in an all-around planetary high-energy ball mill for 2-7 hours, with a ball-to-material ratio of 20:1 and a rotation speed of 330-350 rpm. During the ball milling process, the ball mill is stopped for 0.5 hours every 1 hour of operation.
2. The hydrogen storage composite material according to claim 1, characterized in that, The hydrogen storage composite material contains Mg 90 Ce 3- x La x Ni 7-y-z Be y Cu z The hydrogen storage alloy and a catalyst comprising 4-6 wt% of the alloy, the catalyst comprising ZrF4 and La2O3, wherein 0.5 ≤ x ≤ 2.5, 0.5 ≤ y ≤ 2, and 2 ≤ z ≤ 3.
3. The hydrogen storage composite material according to claim 1, characterized in that, The hydrogen storage alloy has a nanocrystalline structure with an average grain size of 55-100 nm.
4. A method for preparing the hydrogen storage composite material according to any one of claims 1-3, characterized in that, The method includes: S1: Mg is composed according to the preset chemical formula. 90 Ce 3-x La x Ni 7-y-z Be y Cu z When preparing the ingredients, a certain proportion of loss on ignition should be added when weighing Mg, La, and Ce. S2. Place the prepared raw materials in the magnesium oxide crucible in sequence, melt the raw materials by electric arc melting, induction heating melting or other heating methods, and pour the molten alloy into the copper mold to obtain the master alloy ingot. S3. The ingot prepared in S2 is placed in a quartz tube with a slit at the bottom and induction heated until the ingot is completely melted. The pressure of the protective gas is used to spray the liquid alloy from the slit at the bottom of the quartz tube onto the surface of a rotating water-cooled copper roller to form a rapid quenching alloy strip. The linear speed of the water-cooled copper roller is 10-20 m / s and the thickness of the rapid quenching alloy strip is 100-350 μm. S4. After mechanically crushing the rapid-quenched alloy strip and passing it through a 200-mesh sieve, the alloy particles remaining on the sieve are loaded into a ball mill jar together with the catalyst ZrF4+La2O3 and stainless steel grinding balls. After ball milling, Mg-RE(La,Ce)-Ni-Be-Cu based solid hydrogen storage composite material is obtained. The ball milling is carried out in an all-around planetary high-energy ball mill for 2-7 hours, with a ball-to-material ratio of 20:1 and a rotation speed of 330-350 rpm. During the ball milling process, the ball mill is stopped for 0.5 hours every 1 hour of operation.
5. The method according to claim 4, characterized in that, In step S1, Mg, La and Ce are added as an additional 5%-10% of their calculated mass as loss on ignition during batching.
6. The method according to claim 4, characterized in that, In step S2, the specific steps of the melting operation are as follows: the weighed bulk metal is placed in the magnesium oxide crucible of the medium-frequency induction furnace according to the designed process; bulk rare earth elements La, Ce, and electrolytic Cu are placed at the bottom of the crucible; bulk Be and Ni plates are placed on top of the electrolytic Cu; and bulk Mg is placed on the top layer; a vacuum is drawn to 1×10⁻⁶. -2 -5×10 -5 A pressure of 0.01-0.1 MPa is introduced as a protective gas, which is high-purity helium or a helium-argon mixture with a volume ratio of 1:
1. The temperature is then increased to 1500-1600℃ to obtain molten Mg. 90 Ce 3-x La x Ni 7-y- z Be y Cu z Liquid master alloy, hold for 1-5 minutes.
7. The method according to claim 4, characterized in that: In step S3, the linear speed of the water-cooled copper roller is 12-18 m / s.
8. The method according to claim 4, characterized in that, In step S4, the specific steps of ball milling are as follows: after evacuating the ball mill jar, fill it with high-purity argon gas and ball mill for 2-6 hours in an all-around planetary high-energy ball mill.
Citation Information
Patent Citations
High-capacity Mg-Y-Al-Sn-based solid hydrogen storage composite material and preparation method thereof
CN117448606A
Mg-base hydrogen-bearing alloy material and its preparing process and application
CN1316537A
